Travel information and travel choice behaviour - Lim, Chin Kee. (2011)
For a country with scarce resources, it is important for Singapore to have an efficient traffic planning. Further, it is believed that real time traffic information dissemination is an efficient way leading towards an optimal traffic management. With traffic information describing the real time traffic conditions, travellers will probably change their routing choice and departure time accordingly.In addition, the effectiveness of the traffic information on traffic management highly depends on quality